3-D dispersion model for simulation of accidental toxic gas releases in a metropolitan area - Min, Mimi; Park, Junyong; Kang, Chankyu; Jung, Seungho (Journal of Loss Prevention in the Process Industries, 2021)
Computational fluid dynamic (CFD) simulations were performed to assess the potential chlorine leak scenario in the super-urban area of South Korea, where the human population density is very high and numerous buildings exist near operational water treatment facilities. Flame acceleration simulator (FLACS) was used to predict the consequence from accidental chlorine releases out of one of the water treatment facilities for the nearby area having a size of 5 km × 3 km approximately. The ability to precisely implement 3-D geometries is crucial for a successful 3-D simulation. Thus, a method was proposed to rapidly and accurately implement geometry by importing computer aided-design (CAD) files provided by a government agency, and processing them using Auto CAD and MicroStation software programs. An accidental release from an 18-ton tank was simulated with three different wind directions to determine the expected evacuation distances. Results from the study showed that the endpoint distances varied depending on the density and arrangement of the buildings. Moreover, we employed physical barriers with varying heights for mitigating the effects of toxic gas releases and simulated how effectively they decreased the concentration of released chlorine.
Keywords: Accidental release; Dispersion modeling; Flame acceleration simulators; Government agencies; Metropolitan area; Physical barriers; Toxic gas release; Water treatment facilities; Chlorine; Computational fluid dynamic (CFD); Dispersion; Geometry; Human fatality rates; Physical barrier; Toxic gas